RESEARCH ON PROBLEMS AND CONSUMER EXPECTATIONS IN SPORTSWEAR PRODUCTS - Acar, Eda; Guner, Mucella (International Journal of Research -GRANTHAALAYAH, 2025)
Sportswear today is not only preferred for sporting activities but has also become a widely used product group in daily life. This situation makes consumers’ expectations and purchasing behaviors regarding sportswear increasingly significant. This study was conducted to examine the purchasing behaviors of sports center members in the Bornova district of İzmir toward sportswear products, the problems they encounter during use, and their expectations from these products. The survey, carried out with 152 participants, consisted of three sections: demographic characteristics, purchasing behaviors related to sportswear products, and expectations from garments. According to the findings, participants most frequently preferred tops and leggings when purchasing sportswear, with comfort being the primary factor influencing their purchasing decisions. The most commonly reported issues with tops were post-wash deformation, seam unraveling, and color fading, while the main problems with bottoms included rapid deformation, seam splitting, and fabric pilling. In addition, product lifespan, washing durability, air permeability, seam strength and fabric elasticity were identified as the most important expected features of sportswear.